2022
DOI: 10.3390/biom12111553
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Acellular Assay to Study Interactions between Actinides and Biological or Synthetic Ligands

Abstract: Speciation of actinides, and more particularly bioligand-binding ability, influences in vivo behavior. Understanding these interactions is essential for estimation of radiological dose and improvement of decorporation strategies for accidentally contaminated victims. Because the handling of actinides imposes overwhelming difficulties, in vitro assays carried out in physiological conditions are lacking and data regarding such interactions are scarce. In this study, we used a bi-compartmental and dynamic assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In addition, the medium used is a simple salt solution where the main constituent is sodium chloride (140 mM). Previous experiments in this laboratory as well as others have shown that the type of media may influence dissolution ( Ansoborlo et al 1999 ; Aladova et al 2007 ; Bauer et al 2012 ; Garger et al 2013 ; Griffiths et al 2016 ; Van der Meeren et al 2019 , 2022a ). The original report concerned the classification using Ringer’s solution where again the basic constituent is sodium chloride ( Khokhryakov et al 1998 ).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, the medium used is a simple salt solution where the main constituent is sodium chloride (140 mM). Previous experiments in this laboratory as well as others have shown that the type of media may influence dissolution ( Ansoborlo et al 1999 ; Aladova et al 2007 ; Bauer et al 2012 ; Garger et al 2013 ; Griffiths et al 2016 ; Van der Meeren et al 2019 , 2022a ). The original report concerned the classification using Ringer’s solution where again the basic constituent is sodium chloride ( Khokhryakov et al 1998 ).…”
Section: Resultsmentioning
confidence: 59%
“…In this model, different actinides are incorporated into an agarose gel called the static phase and the transfer of activity to the external medium called the dynamic phase is monitored ( Griffiths et al 2016 ; Van der Meeren et al 2019 ). In this approach both phases may be modified to represent fluid compartments (blood, synovial fluid, sweat) or retention compartments (bone, lungs, intracellular) ( Griffiths et al 2016 ; Van der Meeren et al 2022a ). Moreover, this model was shown to correlate well with in vivo data from the laboratory using actinides prepared from the same stocks ( Griffiths et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%